The Impact of Awarding Incentives on Posyandu Cadre Performance - Atik Farokah; Qatrunnada Naqiyyah Khusmitha; Herdian Fitria Widyanto Putri; Eri Kurniasari (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2023)
Background:Stunting is a condition of failure to thrive due to chronic malnutrition that occurs in toddlers. Posyandu is an intervention facility for a specific nutrition program carried out by the Ministry of Health. The role of posyandu cadres is very important in efforts to reduce the prevalence of stunting. The Government of Malang Regency implements a cash incentive program for all posyandu cadres to improve their performance.Objective:This study aims to compare the effect of giving cash incentives on the performance of cadres of Pagelaran Health Center and Gedangan Health Center, Malang Regency.Methods:This study used an observational analytic design using a proportional cluster random sampling technique on 125 Pagelaran Health Center cadres and 125 Gedangan Health Center cadres. The research results were analyzed and interpreted using the SPSS Windows release version 2.1 computer program.Results:The results of this study prove that giving incentives to posyandu cadres in the Pagelaran Health Center work area has no effect on cadre performance with a significance value of 0.98 and giving incentives to posyandu cadres in the Gedangan Health Center work area has no effect on cadre performance with a significance value of 0.657.Conclusion:It can be concluded that the provision of incentives has no direct effect on the performance of posyandu cadres in the work area of Pagelaran Health Center and Gedangan Health Center.